PENGEMBANGAN SOAL TES UNTUK MENGUKUR KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI BENTUK ALJABAR - Tita Elisya Wibowo; Siti Faizah (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Problem-solving ability became a learned process as well as a goal that must be achieved in learned mathematics so it is important for students to have these abilities, especially in algebraic form material. But in fact, in the material of algebraic forms, the ability was still minimally mastered by students. Based on the results of the interview, it shows that the lack of ability was due to the questions given by the teacher only in the form of routine questions taken from LKS or textbooks that did not require the use of problem-solving skills but only require the used of procedural formulas. Therefore, it was necessary to develop test questions that contain question items that could measure students' problem-solving abilities in the algebraic form of material. This type of research was developed researched using the ADDIE model which stands for analysis, design, development, implementation, and evaluation. Data collection techniques used in this study were validation questionnaires and tests. Meanwhile, the data collection instruments were validation questionnaire sheets and test sheets. The test subjects in this study were class VII C students of MTs Salafiyah Syafi'iyah Seblak Jombang. The results showed that the product developed in the form of a test was declared valid by the expert with an average validity of 3.75 and was in very valid criteria. Meanwhile, the results of the empirical validity test showed that only four of the five items on the test developed were declared valid and of the four items that were valid, the reliability value of 0.786 with high criteria was obtained. The research findings prove that the developed test contains only four items that were valid both theoretically and empirically and reliably so that they could be used to measure students' problem-solving abilities on the algebraic form of material.